Study on Optimization of Geothermal Tail Water Reinjection Process in Moderately Deep Sandstone. (11th February 2021) - Li, Hongyan; Wang, Pengtao; Liu, Bin; Zhang, Xianyu; Guo, Shiyan; Xiao, Hui; Huang, Hai
Abstract : The existing test methods of geothermal tail water reinjection effect in sandstone geothermal reservoirs are not suitable for moderately deep and deep sandstone geothermal reservoirs, resulting in the poor filtration performance of fine-grained reservoirs. Therefore, a test method for the geothermal tail water reinjection effect in a moderately deep sandstone geothermal reservoir is proposed. This paper studies the static compatibility of raw water and geothermal tail water under different mixing ratios, determines the indexes affecting the reinjection effect of moderately deep sandstone geothermal reservoir tail water, analyzes the weight set of each influencing factor, and formulates a test standard for the reinjection effect of geothermal reservoir tail water. Finally, a tracer is selected to trace the reinjected tail water in the geothermal reservoir, and the tracer is used to obtain the result of each previously determined index. Eventually, the final reinjection effect of the geothermal tail water is obtained. The experimental results show that the fine-grade filtration performance, silt-grade filtration performance, and coarse-grade filtration performance of this method are improved compared with those of other methods; thus, the particle filtration performance is better, and the reinjection effect of geothermal reservoir tail water is better, which has a great significance for the geothermal resource exploitation of moderately deep sandstone.